Performance of TCP variants over LTE network - Awang Nor, Shahrudin; Maulana, Ade Novia (IP Publishing LLC, 2016)
One of the implementation of a wireless network is based on mobile broadband technology Long Term Evolution (LTE).LTE offers a variety of advantages, especially in terms of access speed, capacity, architectural simplicity and ease of implementation, as well as the breadth of choice of the type of user equipment (UE) that can establish the access.The majority of the Internet connections in the world happen using the TCP (Transmission Control Protocol) due to the TCP’s reliability in transmitting packets in the network.TCP reliability lies in the ability to control the congestion.TCP was originally designed for wired media, but LTE connected through a wireless medium that is not stable in comparison to wired media.A wide variety of TCP has been made to produce a better performance than its predecessor. In this study, we simulate the performance provided by the TCP NewReno and TCP Vegas based on simulation using network simulator version 2 (ns2).The TCP performance is analyzed in terms of throughput, packet loss and end-to-end delay.In comparing the performance of TCP NewReno and TCP Vegas, the simulation result shows that the throughput of TCP NewReno is slightly higher than TCP Vegas, while TCP Vegas gives significantly better end-to-end delay and packet loss. The analysis of throughput, packet loss and end-to-end delay are made to evaluate the simulation.